Pengalaman Manajemen Nyeri pada Pasien dengan PPOK: Studi Kualitatif - Kartika, Imelda Rahmayunia; Renda, Suchi Leona; Saputra, Yoki (REAL in Nursing Journal, 2022)
Background: Chronic obstructive pulmonary disease (COPD) is a common health problem in the community. One of the conditions that will appear in this phase of the disease is chronic pain. This study aims to describe the experiences of patients with COPD about their pain experiences and how they manage their pain. Methods: This study used descriptive qualitative research conducted through an interview process in one of the Jambi Provincial Hospitals, Indonesia. Sampling continued until saturation was reached, resulting in five participants who met the inclusion criteria. Data were collected by interview and analyzed through collaizi analysis. Results: The participants were all male and aged between 60-70 years old. The duration of COPD disease is between 5-20 years. The results of this study found 6 (six) main themes that describe the experience of pain in COPD patients, including experiences regarding the factors that cause pain, pain quality, pain location, pain scale, pain time and pain management. Conclusion: Chronic pain is common in patients with COPD and adversely affects quality of life and participation in daily physical activities. However, several ways of managing pain symptoms can be practiced by patients. The impact of effective pain management is that it will improve the quality of life in people with COPD. There is a need to develop pain management that can be recommended at any stage of patient care. Healthcare providers are advised to provide information to patients on how to manage pain so that they can improve their healthcare.Keywords: pain, COPD patients, qualitative